KESETARAAN GENDER DAN RELASI KUASA DALAM TAFSIR AL-QUR’AN TEMATIK KEMENTERIAN AGAMA REPUBLIK INDONESIA - Purwanto, Tinggal (UIN Sunan Kudus, 2019)
Tafsir Al-Qur’an Tematik is a product of mufassir creative dialectic with the text of the Qur'an which contains interrelated elements among various interests as produced by involving the Government. This engagement raises the question of the supposedly dialectical interpretation, while raising questions about the product of tafsir, especially regarding the interpretation of gender equality which indicates a power-knowledge relations built for a particular interest. This study aims to explain how power-knowledge relations operate in the book, especially in constructing gender equality. With that purpose, the theory of gender equality and the theory of power-knowledge relations is used to achieve the intended purpose. The this study finds that power-knowledge relations flow in the Tafsir Al-Qur’an Tematik. Power relations operate in a dialectical and productive manner through initiation, election, accommodation, contestation, controversy, negotiation and compromise of the exegeteers in compiling the tafsir. The mufassir not only try to explain the book of the Qur'an alone, but also attempt to construct the life of the people to be in line with the Government agenda. The mufassir does attempt to construct an equal relationship between men and women, but the construction is not wholly objective and neutral as it still leaves a more discriminatory effect prioritizing men in the public domain and women in the domestic sphere. These power-knowledge relations operate systematically by controlling power relations with truth so as to give rise to more equitable constructions directed to regulate the lives of people on behalf of increased productivity. By its mechanism, power-knowledge normalizes the lives of people with a construction of gender equality that is essentially loaded with power politics. Keywords: tafsir, gender equality, and power relations.Tafsir Al-Qur’an Tematik is a product of mufassir creative dialectic with the text of the Qur'an which contains interrelated elements among various interests as produced by involving the Government. This engagement raises the question of the supposedly dialectical interpretation, while raising questions about the product of tafsir, especially regarding the interpretation of gender equality which indicates a power-knowledge relations built for a particular interest. This study aims to explain how power-knowledge relations operate in the book, especially in constructing gender equality. With that purpose, the theory of gender equality and the theory of power-knowledge relations is used to achieve the intended purpose. The this study finds that power-knowledge relations flow in the Tafsir Al-Qur’an Tematik. Power relations operate in a dialectical and productive manner through initiation, election, accommodation, contestation, controversy, negotiation and compromise of the exegeteers in compiling the tafsir. The mufassir not only try to explain the book of the Qur'an alone, but also attempt to construct the life of the people to be in line with the Government agenda. The mufassir does attempt to construct an equal relationship between men and women, but the construction is not wholly objective and neutral as it still leaves a more discriminatory effect prioritizing men in the public domain and women in the domestic sphere. These power-knowledge relations operate systematically by controlling power relations with truth so as to give rise to more equitable constructions directed to regulate the lives of people on behalf of increased productivity. By its mechanism, power-knowledge normalizes the lives of people with a construction of gender equality that is essentially loaded with power politics.